RAMP - Research and Market Pathways Kickoff Event - CGIAR Accelerate for Impact Platform (2024)
Have you envisioned your innovative solution thriving beyond the usual research grant period, creating a lasting impact? If so, check out the kickoff event to the new program, RAMP – Research and Market Pathways, which was held on Wednesday 16 October, 2024, at 15:00 CEST.